2002
DOI: 10.1046/j.1523-1755.62.s82.8.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 receptor blockade to control blood pressure in postmenopausal women: Influence of hormone replacement therapy

Abstract: Candesartan cilexetil significantly reduced SBP and DBP and increased control (61.2%) of BP in hypertensive menopausal women. Only age had an inverse association with control of BP. In this study, HRT did not affect the control of BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…However, it is tempting to speculate that the balance of the RAS is shifted postmenopause towards the pressor pathway. Certainly, it is known that plasma renin activity is increased in postmenopausal women compared to premenopausal women [36],[37]. Moreover, AT 1 R antagonism improves vascular function in postmenopausal women who are not receiving hormone replacement therapy [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is tempting to speculate that the balance of the RAS is shifted postmenopause towards the pressor pathway. Certainly, it is known that plasma renin activity is increased in postmenopausal women compared to premenopausal women [36],[37]. Moreover, AT 1 R antagonism improves vascular function in postmenopausal women who are not receiving hormone replacement therapy [38].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 2 recent studies have demonstrated that AT 1 receptor blockade significantly reduces blood pressure in hypertensive postmenopausal women. 43,44 Particularly in light of the disappointing cardioprotective results obtained in several clinical trials with hormone replacement therapy, [45][46][47] the mechanisms underlying the estrogen/Ang II system interaction merit further study for the treatment of hypertension in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the cause of hypertension is not well defined in postmenopausal women. It is believed that an increased androgen/ estrogen ratio can alter the renin-angiotensin system (31). Other possible causes for hypertension are increased endothelin levels, oxidative stress, obesity and stimulation of the sympathetic nervous system (32).…”
Section: Metabolic Syndrome In Menopausal Womenmentioning
confidence: 99%